Normal Fault Hosted Quartz-Scheelite Lodes and Associated Vein Swarm, Glenorchy, NW Otago (The Australasian Institute of Mining and Metallurgy, 2001)
Lower greenschist quartzo-feldspathic schists within the N-S trending Earnslaw Synform of the Upper Wakatipu area are pervaded by late-stage quartz filled extensional and extensional shear fractures, with quartz-scheelite lodes infilling normal faults. Exposed veins/lodes mapped over at least 1000 km2 define a paleoflow system developed during late metamorphic exhumation of the schist. Both veins and lodes have consistent angular relationships to the schist foliation independent of their location on the Earnslaw synform. Unfolding the synform leads to a regional subhorizontal foliation and a systematic set of subvertical quartz veins striking NNW extending over a depth interval >5 km, striking parallel to a set of normal faults hosting the quartz-scheelite lodes. The structures define an extensional regime with s1 sub-vertical, s3 oriented WSW-ENE, a low differential stress, and suprahydrostatic fluid pressures.   The quartz-scheelite lodes (<2 m thick) occupy faults which cross-cut the quartz veins, and are traceable for a few hundred metres, at most. The lodes consist of laminated and/or massive quartz, slivers of crushed and folded schist, random and discontinuous lenses of scheelite with clay selvages separating the lode from relatively undisturbed wallrock schist. Textural evidence suggests that slip developed incrementally with total displacement on faults during lode formation on the order of a few ten's of metres.   The distribution of Glenorchy veins demonstrates broad scale hydrothermal flow through low-permeability schist, channelled within dilatant mesh style structures comprising interconnected shear and extension fractures. Flow through the lodes was likely derived from the greater surrounding area via the interlinked network of fractures and focused into the low displacement shears. Available evidence suggests the system developed together in a uniform extensional stress regime toward the bottom half of the seismogenic regime.